Gottes Herrlichkeit - Fischer, Georg 1954- (2024)
The article reflects on the biblical concept of glory (כבד / δόξα) and details aspects of its theological content by reading relevant passages in their literary contexts. The second part of the article ponders methodological questions of an exegesis that aims at theological insights.
Keywords: roles of the Spirit and prayer; perception of God; approaches to the Bible; Glory; Rolle von Geist und Gebet; Auffassung von Gott; Zugang zur Bibel; Herrlichkeit